COMMUNITY PARTICIPATION: A TOOL FOR SUSTAINABLE COMMUNITY DEVELOPMENT IN ILORIN WEST LOCAL GOVERNMENT AREA, KWARA STATE - MOHAMMED, RAMAT MOPE OPOBIYI; ALAKOSO, IBRAHIM MUSA; MUHAMMED, IBRAHIM (Sokoto Educational Review, 2025)
This paper examines community development as a crucial tool for community growth. The researcher explored several models of community development, including the Elitist model, where proponents believed that community development initiatives should be led by socialist, educated elites and a select group of wealthy individuals. Other models discussed included the incremental gains model and the public awareness model. The paper delved into other key aspects of community development, emphasizing the roles of education and Information and Communication Technology (ICT) in fostering stronger and more vibrant communities over the long term. The researcher concludes by emphasizing the need for a comprehensive community development model that benefits the entire population. This model should incorporate public opinion through mechanisms such as public hearings, public juries, focus group discussions, and referendums to determine the most suitable path for community development. Consequently, the paper recommends that the government establish robust communication channels, conduct regular town hall meetings, enact legislation that reflects the will of the people, implement social intervention programs to assist rural populations, and create employment opportunities for youth. DOI: https://doie.org/10.0225/SER.2025119617